Evolution mechanism of phase transformation of Li-rich cathode materials in cycling. (20th December 2019) - Cui, Shao-Lun; Wang, Yang-Yang; Liu, Sheng; Li, Guo-Ran; Gao, Xue-Ping
Abstract: Conventional Li-rich layered oxides are composed of the intergrowth of LiMO2 R 3 ‾ m and Li2 MnO3 C2/ m phases, and provide high capacity as cathode materials for Li-ion rechargeable battery. However, the mechanism behind capacity and voltage fading still needs further understanding. In this work, based on intensive analysis on crystalline phase and interface of the classical Li-rich cathode material, Li1.2 Ni0.13 Co0.13 Mn0.54 O2 during charge-discharge processes, especially in the initial charge process, evolution mechanism of oxygen loss-induced phase transformation is illustrated in details. The irreversible anionic redox contributes to the large voltage plateau at 4.5 V during initial charging. As a result, oxygen vacancies forming on the surface reduce the barrier of the migration of transition metal ions into Li layer, causing severe cation mixing and initiating the phase transformation from a layered structure to a spinel structure. Meanwhile, the removal of Li + and O 2− from Li2 MnO3 component brings about changes in lattice parameters. The evolution mechanism can be described in stages: starting from the first charge as the initiation stage; Li/transition metal cations mixing will continue to increase due to the existence of oxygen vacancies in the next few cycles, accompanying with accelerated phase transformation process; then it becomes relatively moderate under the protection of CEI film while still with inevitable structural changes over long cycling, reaching the accumulation stage. Graphical abstract: Image 1